A review of silver nanowire-based composites for flexible electronic applications. (1st March 2022) - Sharma, Neha; Nair, Nitheesh M; Nagasarvari, Garikapati; Ray, Debdutta; Swaminathan, Parasuraman
Abstract: Silver nanowires (Ag NWs) have become a ubiquitous part of flexible electronic devices. The good electrical conductivity of silver, coupled with the excellent ductility and bendability exhibited by the wires make them ideal for flexible devices. Additionally, deposited films of Ag NWs are also found to be transparent due to the incomplete areal coverage of the wires. Thus, Ag NWs are widely used as transparent conducting electrodes (TCEs) for flexible and wearable electronics, replacing the traditionally used metal oxide based TCEs. The properties and functionality of NWs can be further improved by forming composites with other materials. Composites have been synthesized by combining Ag NWs with metals, metal oxides, and polymers. Both dry- and wet-techniques have been used to synthesize and deposit these composites, which have unique structural, chemical, and functional properties leading to myriad applications. This review focuses on recent developments in the field of Ag NW-based composites. An overview of the various fabrication techniques is provided, with a particular focus on coating and printing techniques, which are widely used for depositing Ag NWs. The application of the composites in diverse fields is also discussed. While the most common application for these composites is as TCEs, they are also used in sensors (physical, chemical, and biological), displays, and energy-related applications. The structural and environmental stability of the composites is also discussed. Given the wide interest in the development of printed flexible electronic devices, new Ag NW-based composites and application areas can be expected to be developed going forward.